Upin and Ipin: Islamic Educational Values in Contemporary Cartoons Media Discourse - Padli, Erwin; Hafizah Hajimia; Muhammad Taisir (JURNAL PENELITIAN KEISLAMAN, 2024)
The study aims to explore and elucidate two key areas namely the Islamic educational values portrayed in the Upin & Ipin and the series’ contribution to educational discourse. The study employed a literature review methodology and collected data through the documentation of existing sources. Content analysis techniques were utilized to analyze the gathered data. The findings indicate that Upin & Upin exemplifies Islamic educational values such as i’tiqodiyah (faith), evident in themes of gratitude and sincerity; khuluqiyah (good manners), portrayed through honesty, empathy, trust, and mutual assistance; and amaliyah, exemplified through acts of almsgiving and prayer. Furthermore, the series effectively disseminates Islamic educational content and encourages adherence to these values among its audience, thereby underscoring the series’ relevance in educational contexts. The significance of this study is that it provides a Islamic Educational Values in Contemporary Cartoons Media Discourse.